Prostate cancer is not breast cancer - Venniyoor, Ajit (Indian J Med Paediatr Oncol, 2016)
Cancers of the prostate and breast are hormone dependent cancers. There is a tendency to equate them and apply same algorithms for treatment. It is pointed out that metastatic prostate cancer with bone-only disease is a potentially fatal condition with a much poorer prognosis than metastatic breast cancer and needs a more aggressive approach.